2018
DOI: 10.1002/csr.1647
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between corporate social responsibility and sustainable financial performance: firm‐level evidence from Taiwan

Abstract: This study examines the relationship between corporate social responsibility (CSR) and corporate financial performance (CFP) in Taiwan. Using CSR awards as a social responsibility indicator, this study finds that socially responsible firms can achieve financial results superior to those of firms which do not pursue CSR initiatives. The relationship remains after endogeneity is treated. The Google Search Volume Index (SVI) is used as a specific proxy for firm visibility, observing that it has a positive infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
174
4
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(202 citation statements)
references
References 60 publications
15
174
4
9
Order By: Relevance
“…Kim et al () argued that positive CSR helps in achieving high employee commitment, high level of legitimacy from the community, and even better governmental relations. Hou () argued that CSR implementation enhances firm effectiveness through attaining sustainable performance. A recent study conducted by Wang, Chen, Yu, and Hsio () also demonstrated significant positive impact of CSR on firm's performance.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al () argued that positive CSR helps in achieving high employee commitment, high level of legitimacy from the community, and even better governmental relations. Hou () argued that CSR implementation enhances firm effectiveness through attaining sustainable performance. A recent study conducted by Wang, Chen, Yu, and Hsio () also demonstrated significant positive impact of CSR on firm's performance.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In literature, voice behavior, task significance, job autonomy efforts, job security, justice, healthy working relationship, and citizenship behavior have been reported as possible outcomes of EL (Mostovicz, Kakabadse, & Kakabadse, 2009;Roeck & Farooq, 2018). As for CSR, it may bring numerous paybacks to an organization and its stakeholders in terms of competitive advantage and arrival of new institutional investors (Castro-González, Bande, & Kimura, 2019;Hou, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Institutional transitions affect the role of financial performance in CSR reporting CFP buffers against external pressures on CSR brought by institutional transitions Hou (2019) Relationship between CSR and CFP in Taiwan Socially responsible firms can achieve financial performance superior to those which do not pursue CSR initiatives Hussain et al (2018) Link between sustainability practices and CFP Interlinks between different sustainability performance dimensions and subdimensions are weak and somewhat contradictory to bias and fragment research results Lu et al (2018) Link between CSR and its material implications including CFP CSR programs can be detrimental to CFP in the short term but conducive to improving it in the long term Busch and Friede (2018) Relation between CSP and CFP The relation is positive regardless of whether firms focus on ecological or social aspects. Strong relation for operational, short-term CFP Marti et al…”
Section: Significant Differences Between Industrial Firms and Financimentioning
confidence: 99%
“…However, these studies showed inconsistent conclusions regarding the relationship between CSR and corporate financial performance (Hou, 2018;Orlitzky, Schmidt, & Rynes, 2003;Uadiale, Temitope, & Fagbemi, 2012;Yang, Lin, & Chang, 2010). However, these studies showed inconsistent conclusions regarding the relationship between CSR and corporate financial performance (Hou, 2018;Orlitzky, Schmidt, & Rynes, 2003;Uadiale, Temitope, & Fagbemi, 2012;Yang, Lin, & Chang, 2010).…”
Section: Introductionmentioning
confidence: 99%